SKRINING FITOKIMIA DAN UJI TOKSISITAS EKSTRAK DAUN PECUT KUDA (Stachytarpheta jamaicensis L. Vahl) TERHADAP LARVA UDANG Artemia salina Leach - Lany Indrayani; Hartati Soetjipto; Lydia Sihasale (The East Java Biological Society, 2006)
Phytochemical screening and Brine Shrimp lethality test of pecut kuda leaf extract had been done against Artemia salina Leach. The aims of this study is to screen potentially bioactive extract of pecut kuda leaf as an effort ti find out the chemical substances responsible for the toxic effect. The Pecut kuda leaves (Stachytarpheta jamaicensis, L. Vahl) was extracted by methanol 80%, then partitioned successively with hexane, chloroform, and ethyl acetate. Phytochemical screening was done according to Ciulei method (1984). The toxicity effect was tested against A. salina, L (Brine Shrimp Test). The result of phytochemical screening known that compounds in the extract of pecut kuda leaves (S. jamaicensis, L. Vahl), hexane fraction contained of sterol and triterpenes; where the chloroform fraction contained of saponin, sterol, and triterpenes; further more the ethyl acetate fraction contained flavonoid, tannin, saponin, sterol, dan triterpenes. The result of the study shows that several fractions of extract of pecut kuda leaves (S. jamaicensis) hexane fraction, chloroform, and ethyl acetate was toxic because it was able to kill more than 50% larva of A. salina, L at the concentration less than 1000 ppm. The LC50 of all fractions of pecut kuda leaves extract (S. jamaicensis, L. Vahl) were shown from the most toxic to the lowest were as followed: LC50 of hexane fraction = 98.33 ppm, of chloroform raction LC50 = 204.17 ppm, and of ethyl acetate fraction LC50 = 249.80 ppm. Finally results of the TLC profile showed that all fraction (hexane, chloroform, and ethyl acetate) indicated that the pecut kuda leaves extract (S. jamaicensis) contained terpenoid compound.